# log[5](45x)-log[5](3)=1

## Simple and best practice solution for log[5](45x)-log[5](3)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for log[5](45x)-log[5](3)=1 equation:

Simplifying
log[5](45x) + -1log[5](3) = 1
Remove parenthesis around (45x)
glo * 5 * 45x + -1log[5](3) = 1
Reorder the terms for easier multiplication:
5 * 45glo * x + -1log[5](3) = 1
Multiply 5 * 45
225glo * x + -1log[5](3) = 1
Multiply glo * x
225glox + -1log[5](3) = 1
Reorder the terms for easier multiplication:
225glox + -1 * 5 * 3glo = 1
Multiply -1 * 5
225glox + -5 * 3glo = 1
Multiply -5 * 3
225glox + -15glo = 1
Reorder the terms:
-15glo + 225glox = 1
Solving
-15glo + 225glox = 1
Solving for variable 'g'.
Move all terms containing g to the left, all other terms to the right.
Reorder the terms:
-1 + -15glo + 225glox = 1 + -1
Combine like terms: 1 + -1 = 0
-1 + -15glo + 225glox = 0
The solution to this equation could not be determined.`